Performance Assessment of an Air-Type BIPVT Collector with Perforated Baffles through Indoor and Outdoor Experiments - Jin-Hee Kim; Ji-Suk Yu; Erin Gaucher-Loksts; Benjamin Roy; Véronique Delisle; Jun-Tae Kim (Energies, 2022)
The performance of air-type PVT and BIPVT collectors has been extensively studied. As a system that generates heat and power, PVT collector testing has some particularities especially when using air as a heat recovery fluid and a building-integrated design (BIPVT). The electrical and thermal experimental performance of such collectors are currently being evaluated using in-house methods or PV and/or solar thermal collector standards. The use of a wide range of methods, testing conditions and experimental setups makes it difficult not only to compare the performance of different designs, but also to have confidence in the results obtained. This study evaluates the performance of an air-type BIPVT collector with in-channel perforated baffle plates for heat transfer enhancement designed for a building-integrated façade. As part of a joint research project between Korea and Canada, the proposed collector’s performance was evaluated through indoor (Canada) and outdoor experiments (Korea). Limited comparison of the results obtained with the two testing methods could be performed due to differences in environmental testing conditions, BIPVT collector area and experimental setup. Nevertheless, the limited measurement points under comparable testing conditions indicate that the results from the indoor and outdoor experiments have a similar trend. A comparison between the studied collector having a full PV absorber and a BIPVT collector with a hybrid PV/solar thermal collector absorber using a similar indoor experimental setup and testing conditions was performed. It showed that under still air conditions, for an irradiance level of approximately 820 W/m2 and with a low flow rate, the BIPVT collector with a hybrid PV/solar thermal absorber has a thermal and electrical efficiency of 25.1% and 5.9%, respectively. Under similar conditions, the BIPVT collector with a full PV absorber has a thermal efficiency of 23.9% and an electrical efficiency of 13.5%. At higher flowrates, both units have similar thermal efficiencies, however, the BIPVT collector with a PV absorber remains with an electrical efficiency that is more than double that of the unit with a hybrid PV/solar thermal absorber.